An investigation of base flow control by wall pressure analysis in a suddenly expansion nozzle - Khan, Sher Afghan; Bashir, Musavir; G M, Fharukh Ahmed; Ullah, M. Asad (UNIV LAGOS, 2016)
This paper presents the results of an experimental investigation conducted at supersonic Mach number of 1.25 through a converging–diverging nozzle for diameter-ratio of 1.6. The experiments were conducted at different level of expansion viz. for correctly expanded and under expanded cases and, for length-to-diameter ratio of 10 to 1. From the results it is found that the flow remains attached with the suddenly expanded duct even for L/D = 1 for both with and without control cases. For some combination of the NPR and L/D ratio the flow field in the duct becomes oscillatory which; indicates that the flow in the duct is dominated by the waves however, it remained same even when the control in the form of micro jets are activated. Hence, the control does influence the flow in the duct wall. It is also seen that when the jets are under expanded the control becomes effective; however, with further increase in the level of under expansion they do not give the desired result. Hence, there seems to be a limiting value of level of expansion which will give desired result and at Mach 1.25, this value is Pe/Pa = 1.5.